Growth and Yield of Carrot Plants (Daucus carota L.) in Combined Doses of Chicken Cage Organic Fertilizer and NPK Inorganic Fertilizer: Pertumbuhan dan Hasil Tanaman Wortel (Daucus carota L.) pada Dosis Kombinasi Pupuk Organik Kandang Ayam dan Pupuk Anorganik NPK - Chosim, Nanang; Purnamasari, Retno Tri; Hidayanto, Fajar (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2024)
Demand for vegetable commodities, including carrots, is high due to the increasing population and increasing public awareness of nutritional value, the need for food consumption is also increasing. The purpose of this study was to obtain the right dose of combination of chicken coop organic fertilizer and pearl npk inorganic fertilizer to support the growth and yield of carrot plants. The method used in this study was a randomized group design (RAK) with 4 treatments and each treatment was repeated 6 times. The treatment made is P0: 100% NPK Mutiara (75 kg ha-1); P1: Chicken manure dose 20 tons ha-1 + 50 % NPK; P2: Chicken manure dose 25 tons ha-1 + 50 % NPK; P3: Chicken manure dose 30 tons ha-1 + 50 % NPK. Research results The results showed that dosing treatment of 30 tons ha-1 + 50% NPK Plants-1 can increase the growth and highest yield of carrot plants compared to other treatments.